Дослідження впливу градієнту швидкості потоку емульсії на якість диспергування молока в імпульсному гомогенізаторі - Паляничка, Надія Олександрівна; Самойчук, Кирило Олегович; Ялпачик, Володимир Федорович; Ковальов, Олександр Олександрович; Червоткіна, Олександра Олександрівна; Palianychka, Nadiia; Samoichuk, Kyrylo; Yalpachyk, Volodymyr; Kovalov, Oleksandr; Chervotkina, Oleksandra (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: У статті розглянуто результати дослідження впливу градієнта швидкості потоку на ступінь диспергування молочної емульсії в імпульсному гомогенізаторі. Було проведено аналіз основних чинників, що визначають ефективність гомогенізації, і виявлено, що одним із ключових параметрів є градієнт швидкості потоку. Його значення обчислювали методом комп’ютерного моделювання з використанням програмного комплексу кінцево-елементного аналізу Ansys Workbench. Дослідження показали, що найвищий градієнт швидкості виникає на виході з другого поршня-ударника імпульсного гомогенізатора, досягаючи 2,2–5 м/с, що забезпечує необхідний рівень диспергування молочної емульсії. Таким чином, імпульсні гомогенізатори можуть ефективно застосовуватися в технологічних процесах виробництва питного молока. /// EN: The article examines the results of a study on the influence of the velocity gradient of the flow on the degree of dispersion of milk emulsion in a pulsation homogenizer. Homogenization is one of the key technological processes in the dairy industry. With the development of technologies, stricter requirements are imposed on the dispersity of the final product for the components subject to homogenization. The main technical challenge in obtaining finely dispersed emulsions remains the limited capabilities of modern homogenizers. The most common type of equipment used in modern enterprises is the valve homogenizer. They provide high-quality dispersion of emulsions, but are characterized by significant energy consumption during the process, exceeding 7 kW/t. Therefore, the development of new devices and methods for obtaining finely dispersed emulsions with the possibility of adjusting dispersity and ensuring high productivity is extremely relevant. Analysis has shown that a promising method for obtaining a high-quality product is pulsation homogenization. The study established that the efficiency of homogenization in a pulsation homogenizer is directly determined by the velocity gradient of the milk emulsion flow, which is formed in the working chamber of the apparatus. The values of the velocity gradient of the milk emulsion flow were determined by computer modeling using the finite element analysis software package Ansys Workbench. The calculations showed that the maximum velocity gradient of the milk flow (2.2–5 m/s) occurs at the outlet of the conical openings of the second piston-impactor, which creates conditions for the most efficient homogenization compared to existing homogenizers. Therefore, the use of a pulsation homogenizer is appropriate for dispersing milk emulsion in technological lines of drinking milk production.
Study of the Influence of Emulsion Flow Velocity Gradient on the Quality of Milk dispersion in a Pulsation Homogenizer
Keywords: гомогенізація; градієнт швидкості потоку; Ansys Workbench; робоча камера; молоко; homogenization; flow velocity gradient; working chamber; milk